2013
DOI: 10.1093/infdis/jit103
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Modulates the Fungal Immune Response in Phagocytic Cells From Patients With Chronic Granulomatous Disease

Abstract: Invasive aspergillosis is a major threat to patients with chronic granulomatous disease (CGD). Fungal pathogenesis is the result of a diminished antifungal capacity and dysregulated inflammation. A deficient NADPH-oxidase complex results in defective phagolysosomal alkalization. To investigate the contribution of defective pH regulation in phagocytes among patients with CGD during fungal pathogenesis, we evaluated the effect of the acidotropic, antimalarial drug chloroquine (CQ) on the antifungal capacity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…11 CQ interferes with the formation of autolysosome by increasing the pH in the cells. Previous studies have shown that pH also affect the growth of A. fumigatus, 39 which may be the cause of decreased fungal loads in our study. These three interventions are not specific to autophagy and may affect the fungal load through other pathways.…”
Section: Discussionsupporting
confidence: 47%
“…11 CQ interferes with the formation of autolysosome by increasing the pH in the cells. Previous studies have shown that pH also affect the growth of A. fumigatus, 39 which may be the cause of decreased fungal loads in our study. These three interventions are not specific to autophagy and may affect the fungal load through other pathways.…”
Section: Discussionsupporting
confidence: 47%
“…In addition to the antimalarial and antibacterial effects, HCQ also exhibits antifungal activities. Henriet et al, conducting an in vivo study with Aspergillus fumigatus and Aspergillus nidulans, demonstrated that chloroquine may increase the antifungal activity of leucocytes isolated in those with chronic granulomatous disease (CGD) at a low concentration through regulating the production of interleukin-1β and tumor necrosis factor-α [16]. Another in vitro study also found the synergistic effect of chloroquine and fluconazole against fluconazole-resistant Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…NOX2 activation is accompanied by an influx of K + ions and a rise in pH, which, in turn, is linked to activation of primary granular proteases that are predicted to enhance intracellular killing [34]. In support of this model, chloroquine, a lysosomotropic agent that prevents endosomal acidification, increased the antifungal activity of neutrophils from CGD patients [35]. …”
Section: Activation Of Neutrophil Proteases and Neutrophil Extracellumentioning
confidence: 99%